Effects of precooling on 30-km cycling performance and pacing in hot and temperate environments - Maia-Lima, A.; Ramos, G. P.; Moraes, M. M.; Pacheco, D. A. S.; de Oliveira, G. G. A.; de Barros, C. L. M.; Prado, L. S.; Garcia, E. S. (International Journal of Sports Medicine, 2017)
This study examined the effects of precooling on performance and pacing during 30-km cycling exercise in hot and temperate environments. 8 trained male cyclists performed 4 trials involving either cooling (PRECTEMP and PRECHOT) or no-cooling interventions (TEMP and HOT) prior to a 30-km self-paced cycling exercise in either a hot (35°C, 68% relative humidity) or temperate environment (24°C, 68% relative humidity). Exercise time was longer in HOT (60.62±3.47?min) than in TEMP (58.28±3.30 min; P<0.001), and precooling attenuated this thermal strain performance impairment (PRECHOT 58.28±3.30 min; P=0.048), but it was still impaired compared with TEMP (P=0.02). Exercise performance in PRECTEMP (54.58±4.35 min) was no different from TEMP. Initial power output was sustained until the end of the exercise in both TEMP and PRECTEMP, but was reduced from the 12th km until the end of the trial in HOT (P<0.05). This reduction was delayed by precooling because power output was reduced only after the 20th km during PRECHOT (P<0.05). Heart rate was similar in all conditions throughout almost the entire exercise, suggesting the maintenance of similar relative intensities. In conclusion, precooling was effective in attenuating, but not completely reversing thermal strain performance impairment and offered no ergogenic effect in the temperate environment.